2014
DOI: 10.3390/rs6043247
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Diurnal Cycle of Land Surface Temperature at High Temporal and Spatial Resolution from Clear-Sky MODIS Data

Abstract: Abstract:The diurnal cycle of land surface temperature (LST) is an important element of the climate system. Geostationary satellites can provide the diurnal cycle of LST with low spatial resolution and incomplete global coverage, which limits its applications in some studies. In this study, we propose a method to estimate the diurnal cycle of LST at high temporal and spatial resolution from clear-sky MODIS data. This method was evaluated using the MSG-SEVIRI-derived LSTs. The results indicate that this method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 34 publications
3
61
0
Order By: Relevance
“…Using the aforementioned 946 cloud-free TIGR atmospheric profiles, we first used the new high accurate atmospheric radiative transfer model MODTRAN 5.2 to simulate the band effective atmospheric transmittance, and then we obtained the coefficients through regression, which resulted in c0 = −9.674, c1 = 0.653 and c2 = 9.087. The model analysis indicated that this method will obtain a CWV RMSE of about 0.5 g/cm 2 . The details about the CWV retrieval can be found in [40].…”
Section: Determination Of Atmospheric Cwvmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the aforementioned 946 cloud-free TIGR atmospheric profiles, we first used the new high accurate atmospheric radiative transfer model MODTRAN 5.2 to simulate the band effective atmospheric transmittance, and then we obtained the coefficients through regression, which resulted in c0 = −9.674, c1 = 0.653 and c2 = 9.087. The model analysis indicated that this method will obtain a CWV RMSE of about 0.5 g/cm 2 . The details about the CWV retrieval can be found in [40].…”
Section: Determination Of Atmospheric Cwvmentioning
confidence: 99%
“…Currently, LST can only be obtained over large spatial and temporal scales through remote sensing data, which have attracted much attention in the last three decades [2,3]. Consequently, many LST retrieval methods have been proposed from remotely sensed data, particularly multi-channel thermal infrared (TIR) data, and these methods can be roughly grouped into three categories: the single-channel algorithm, multi-channel methods (e.g., the split-window algorithm [4][5][6] and the temperature and emissivity separation method [7]) and multi-time methods (e.g., the temperature-independent spectral indices method [8], two-temperature method [9,10] and the physical day and night algorithm [11]).…”
Section: Introductionmentioning
confidence: 99%
“…The LSTs under cloudy skies are not validated due to the lack of in situ measurements and remotely sensed data from other sources. Validation of LSTs at the satellite pixel scale is challenging because LSTs can vary significantly within a pixel and change within relatively short time periods [21]. However, the LSTs are generally similar to neighboring pixels.…”
Section: Application To Actual Msg-seviri Satellite Datamentioning
confidence: 99%
“…As discussed by Duan et al [20][21][22], the DTC model can only be used to describe the LST diurnal cycle under cloud-free skies, i.e., the LST estimated using Equation (8) denotes the LST under cloud-free conditions. If the sky is overcast, the LST daily evolution cannot be determined using the ΔS is calculated using Equation (14) The following prior information is assumed: (1) the fitted LST is equal to or slightly higher than the actual LST; (2) the observations collected before a cloud first appears or at some time (assumed to be 2 h in this study) after a cloud disappears are given higher weights (set to 2), while other observations under cloud-free conditions are given lower weights (set to 1).…”
Section: Determining Parameters In the Dtc Modelmentioning
confidence: 99%
“…Retrievals using radiances from the Moderate Resolution Imaging Spectroradiometer (MODIS) have been both the target and standard for a number of LST verification studies (Wan et al, 2002(Wan et al, , 2004Coll et al, 2009;Jiménez et al, 2012). Duan et al (2014) used four daily observations from Terra and Aqua MODIS to capture the diurnal cycle of LST, which is critical for full characterization of the climate system. Wang et al (2014) conducted a three-way T s comparison using MODIS, in situ ground observations, and model simulations.…”
mentioning
confidence: 99%